Centrifugally driven convection in the rotating cylindrical annulus with modulated boundaries - M. Westerburg; F. H. Busse (Nonlinear Processes in Geophysics, 2003)
The effect of sinusoidally modulated conical end boundaries on convection in a rotating cylindrical annulus is investigated theoretically and experimentally. A quasiperiodic time dependence of convection in the form of thermal Rossby waves is found and semi-quantitative agreement between theory and measurements can be established. The results are relevant to convection in the Earth's outer core close to the tangent cylinder touching the inner core at its equator.